LEGITIMATION/DELIGITAMATION OF INSTITUTIONAL CHANGE - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
A series of «color revolutions» in the post-Soviet space, the events of «Arab Spring» set a new political order. Political institutions have changed and new political procedures and mechanisms for the functioning of the political regime have been put in place. The new political order had to be legitimized, but for this it was necessary to solve those crisis problems that gave impetus to radical changes in society. Typically, a number of factors are causing crises and overcoming the crisis, it is necessary to introduce a system of measures that will provide institutional legitimacy. At the same time, along with legitimation, processes of de-legitimation may take place.